An 'Arms Race' between the Nonsense-mediated mRNA Decay Pathway and Viral Infections. (March 2021) - Leon, Kristoffer; Ott, Melanie
Abstract: The Nonsense-mediated mRNA Decay (NMD) pathway is an RNA quality control pathway conserved among eukaryotic cells. While historically thought to predominantly recognize transcripts with premature termination codons, it is now known that the NMD pathway plays a variety of roles, from homeostatic events to control of viral pathogens. In this review we highlight the reciprocal interactions between the host NMD pathway and viral pathogens, which have shaped both the host antiviral defense and viral pathogenesis.